A power electronic controlled dump load with negligible harmonics for accurate loading used in testing small wind turbines - Klumpner, Christian; Al, Baydu; Hann, David B. (2010)
Permanent magnet synchronous generators (PMSG) are at the core of small scale wind power generators manufactured by a wide range of manufacturers in different configurations: vertical or horizontal axis blades, with various geometries and aerodynamics of the blades; by installing these small scale wind turbines in very large numbers at household levels, it is expected that these will make a positive contribution to the increase of renewable energy generation, reducing the use of fossil fuels that are blamed for climate change. However, a proper evaluation of the technical specification of these small scale wind generators in various weather conditions is necessary in order to assess the full potential of benefits. This paper reports on the implementation and testing of a power electronic dump load that allows continuously adjustable loading of a PMSG with sinusoidal currents and have the capability to self synchronize to its frequency/speed whilst avoiding transient/loosing of synchronism.